The Impact of E-Wom, Shopping Lifestyle, and Sales Promotion on Online Impulsive Buying of Cosmetic Products at Shopee Marketplace - Prakasiwi , Linda; Nuvriasari, Audita (LifeSciFi, 2024)
This study aims to analyze the impact of E-Wom, Shopping Lifestyle, and Sales Promotion on Online Impulsive Buying of Cosmetic Products at Shopee Marketplace. The sample used was 100 respondents with a sampling technique in the form of Purposive Sampling. Based on the results of multiple linear regression analysis tests and hypothesis testing with the t test, the results of this study prove that: (1) E-Wom has a significant positive effect on Online Impulsive Buying of Cosmetic Products at Marketplace Shopee, (2) Shopping Lifestyle has a significant positive effect on Online Impulsive Buying of Cosmetic Products at Marketplace Shopee, (3) Sales Promotion has a significant positive effect on Online Impulsive Buying of Cosmetic Products at Marketplace Shopee..